Analisis Manajemen Risiko Dengan Metode HIRARC Pada Laundry (Studi Kasus Pada Usaha Bobo Laundry) - Sheilla Yullia Febrianti; Fakhrizal Labib Musyaffa; Aulia Zahra; Ali Akbar Alkatili; Indra Satria Nugraha; Syti Sarah Maesaroh (Pusat Riset dan Inovasi Nasional, 2023)
Increasingly advanced technology helps save time and makes work more practical, one of which is in the household sector. This is an opportunity for MSME actors to open a business in the form of laundry services. Laundry is a business sector that provides services by providing clothes washing services, the laundry business has great opportunities because of the development of lifestyles and the level of community mobility which prioritizes practicality in the need for clean clothes. community activities in it which are increasingly diverse, encourage the desire to streamline household activities. One of them is handling dirty clothes at home. For the upper middle class and businessmen who are often found in Tasikmalaya City, the community entrusts the work to laundry services. With the increasing needs of the public using laundry services, good service quality for customers is something that is very important for laundry entrepreneurs to pay attention to. This research focuses on risk management in laundry to minimize the impact of losses.